Uniqueness and Stability Results for Non-local Impulsive Implicit Hadamard Fractional Differential Equations - Karthikeyan, P.; Arul, R. (Journal of Applied Nonlinear Dynamics, 2026)
We analyze the uniqueness and Ulam stability results for implicit impulsive fractional differential equations connecting nonlocal form of the Hadamard derivative of fractional order ϑ. The main results are studied by using the Banach contraction principle and Ulam stability. The finding of the result evoluted by the example.